2001
DOI: 10.1124/mol.59.5.1119
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity p38 Kinase Activity Is Critical for p21cip1 Induction and the Antiproliferative Function of Gi Protein-Coupled Receptors

Abstract: G protein-coupled receptors can stimulate the p38 kinase cascade, but the effect this has on cell growth remains poorly characterized. Here we show human somatostatin sst(2) and sst(4) receptors inhibit basic fibroblast growth factor (bFGF)-induced proliferation, via a mechanism that was blocked by the p38 inhibitor PD 169316. The sst(4) receptor could also induce a proliferative activity in the absence of bFGF, which was unaffected by PD 169316. In contrast, the sst(3) receptor had no effect on basal cell gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 40 publications
2
40
0
1
Order By: Relevance
“…This might explain the opposite effects because growth inhibition by persistent signaling has been described for several G proteincoupled receptors. Examples are gonadotrophin-releasing hormone (GRHR), somatotrophin (sst2), and M3 muscarinic acetylcholine (29)(30)(31) receptors that cause persistent activation of the mitogenactivated protein kinases extracellular signal-regulated kinase 1/2, p38, and c-Jun NH 2 -terminal kinase, respectively. Whereas the growth-promoting M2 and sst3 receptors are rapidly degraded after internalization, the M3 and sst2 receptors are rapidly recycled to the surface (32,33), which is a likely explanation for the persistence of the signals.…”
Section: Discussionmentioning
confidence: 99%
“…This might explain the opposite effects because growth inhibition by persistent signaling has been described for several G proteincoupled receptors. Examples are gonadotrophin-releasing hormone (GRHR), somatotrophin (sst2), and M3 muscarinic acetylcholine (29)(30)(31) receptors that cause persistent activation of the mitogenactivated protein kinases extracellular signal-regulated kinase 1/2, p38, and c-Jun NH 2 -terminal kinase, respectively. Whereas the growth-promoting M2 and sst3 receptors are rapidly degraded after internalization, the M3 and sst2 receptors are rapidly recycled to the surface (32,33), which is a likely explanation for the persistence of the signals.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that SOCS-1 increased and sustained the activation of p38 HOG in response to TNFa in murine ®broblasts, a response that was impaired in SOCS-1 de®cient cells (Morita et al, 2000). Although the pathway by which SOCS-1 couples to p38 HOG is unknown, activation of p38 HOG may be one mechanism of how SOCS-1 arrests cells transiting the cell cycle (Alderton et al, 2001;Bulavin et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that in response to SB203580 treatment, expression of USP22 and the key regulator of cell cycle, p21, exhibited the inverse trend. A previous study has demonstrated that p38 MAPK participates in p21 upregulation, subsequently inhibiting cell growth (21). It is not fully understood how activated p38 MAPK can upregulate p21 expression.…”
Section: A C Bmentioning
confidence: 99%